PERSEPSI MASYARAKAT DESA TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DESA DI DESA LAMAHALA JAYA KECAMATAN ADONARA TIMUR, KABUPATEN FLORES TIMUR - Maryono; Nurcahyat Abdurahman; herni Sunarya (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2020)
This study aims to find out the perceptions of the village community on accountability in the planning, implementation and reporting of village financial management in Lamahala Jaya Village, East Adonara District, East Flores Regency. The type of research used in this study is quantitative research using a descriptive approach. Data obtained from questionnaires / interviews, interviews, and documentation. The sample used was 60 respondents who were taken based on the sampling technique by means of "Cluster Sampling" namely Community Leaders, Customary Leaders, Religious Figures, Educational Figures, Youth Figures, and five ordinary people in each hamlet. Based on the data analysis, it was concluded that the community strongly agreed with the accountability in village financial management planning, accountability in the implementation of village financial management, and accountability in reporting the village financial management by the Lamahala Jaya Village Government. The Village Government is expected to involve the community more in participating in submitting proposals for village financial management planning, more transparent to the public regarding how much the budget is, how the budget is used, and accountability for the budget so that the community can find out and supervise the work of the Village Government, and be more open in providing information about reporting village financial management so that people do not feel confused, and to maintain public trust in the Village Government.